Gambaran Kelengkapan Resep Secara Administratif dan Farmasetik di Apotek K24 Pos Pengumben - Nurwulan Adi Ismaya; Ita La Tho; Muhammad Iqbal Fathoni (STIKes Kharisma Persada, 2019)
In the prescription service flow, pharmacists are required to do prescription screening which includes administrative screening, pharmaceutical suitability and clinical considerations. The administrative and pharmacetic aspects of the prescription were chosen because it was the initial screening when the recipe was served at the pharmacy because it included all the information in the recipe relating to the clarity of the drug writing, the validity of the recipe, and the clarity of the information in the recipe. This research was conducted to find out how the administrative and pharmacetic prescriptions at the Kumbum Pos Pengumben Pharmacy in the period of August to December 2018 fulfilled the prescription completeness according to Minister of Health Regulation No. 73 of 2016. Administrative and pharmacy checks were carried out on 288 prescription sheets by filling in the tables Data collection (Checklist) in accordance with the completeness aspects reviewed. From the results of the study showed the incidence of incomplete prescriptions at the Post-Pengumben K-24 Pharmacy namely 99% body weight, 36% sex, 28% patient age, 1% patient name, 6% doctor name, 28% SIP, as many as 1%, telephone number as much as 15%, initial as much as 53%, prescription date as much as 2%, preparation as much as 25%, dosage strength 24%, drug stability 1%, and 0% compatibility. The complete prescription at the K-24 Pharmacy Station Post has not fulfilled the administrative and pharmaceutical requirements in accordance with Permenkes No. 73 of 2016.